Quantitative ethnobotany of mangrove plant uses by the coastal community of Sicanang Belawan, North Sumatra, Indonesia - ETTI SARTINA SIREGAR; ERNI JUMILAWATY; MASITTA TANJUNG; IWAN RISNASARI; MOHAMMAD BASYUNI; ADE SYAFITRI; ADRIAN HARTANTO (Society for Indonesian Biodiversity, 2025)
Abstract. Siregar ES, Jumilawaty E, Tanjung M, Risnasari I, Basyuni M, Syafitri A, Hartanto A. 2025. Quantitative ethnobotany of mangrove plant uses by the coastal community of Sicanang Belawan, North Sumatra, Indonesia. Biodiversitas 26: 5181-5194. Sicanang Belawan, North Sumatra, Indonesia, harbors a mosaic of coastal and mangrove ecosystems that support local livelihoods. However, unsustainable extraction and the decline of ecotourism threaten both biodiversity and Traditional Ecological Knowledge (TEK). This study aimed to document mangrove plant species utilized by the Sicanang Belawan community and to apply quantitative ethnobotanical indices to identify species of cultural and livelihood significance. Fieldwork was conducted between November 2024 and January 2025 in Belawan Sicanang Sub-district, Medan, North Sumatra, Indonesia. Ethnobotanical data were obtained through structured and open-ended interviews with 71 informants selected by snowball sampling. Plant species were identified through guided forest walks and voucher specimens deposited at Herbarium Medanense (MEDA). Quantitative indices, including Relative Frequency of Citation (RFC), Cultural Importance (CI), Relative Importance (RI), and Cultural Value for ethnospecies (CVe), were calculated. The respondent pool was predominantly female (60.6%), though men reported significantly more plant uses. No significant differences were observed among age or occupation groups. A total of 19 plant species from 10 families were recorded. Fruits (32.43%), leaves (31.75%), and trunks (30.96%) were the most commonly used parts. The main use categories were food (185 reports), construction (176), animal fodder (104), fuel (96), and medicine (89). Nypa fruticans ranked highest across all indices (RFC: 0.887, CI: 2.535, RI: 0.929, CVe: 1.350), followed by Acanthus ilicifolius, highlighting their central role in livelihood, health, and material culture. These findings demonstrate the continued reliance of coastal communities on mangrove resources and highlight the value of traditional ecological knowledge in sustaining local livelihoods. Incorporating such knowledge into community-based conservation and mangrove management can strengthen ecological resilience and ensure the long-term sustainability of coastal ecosystems.